1992
DOI: 10.1007/bf00174117
|View full text |Cite
|
Sign up to set email alerts
|

Influence of azelastine and some selected drugs on mucociliary clearance

Abstract: The effect of azelastine and some selected compounds on ciliary beating frequency (CBF) was investigated in vitro using human mucosal samples and in vivo using anesthetized guinea pigs. Further influence of azelastine on mucus secretion was evaluated in mice and on mucociliary clearance in anesthetized rabbits. Azelastine influenced the ciliary beating frequency neither in vitro nor in vivo. Azelastine, similarly to salbutamol, ambroxol, and bromhexine, increased mucus secretion measured by the tracheal output… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Studies investigating the influence of intranasal antihistamines on mucociliary clearance and ciliary function have provided contradictory results (Table 2). Some studies have demonstrated no adverse effects of intranasal formulations containing azelastine or levocabastine on mucociliary clearance and/or ciliary function, either in vivo or in vitro 1920. In contrast, others have reported that intranasal formulations containing azelastine and levocabastine do produce ciliotoxic effects on human nasal epithelium in vitro 2122.…”
Section: Effects Of Intranasal Antihistaminesmentioning
confidence: 99%
“…Studies investigating the influence of intranasal antihistamines on mucociliary clearance and ciliary function have provided contradictory results (Table 2). Some studies have demonstrated no adverse effects of intranasal formulations containing azelastine or levocabastine on mucociliary clearance and/or ciliary function, either in vivo or in vitro 1920. In contrast, others have reported that intranasal formulations containing azelastine and levocabastine do produce ciliotoxic effects on human nasal epithelium in vitro 2122.…”
Section: Effects Of Intranasal Antihistaminesmentioning
confidence: 99%
“…Both azelastine and levocabastine may cause irreversible ciliostasis at therapeutic concentrations and cause reversible decreases of cilia beating at diluted concentrations [65]. Other studies support the ciliostatic effects of azelastine [66][67][68] while two other studies suggest that azelastine itself may not be ciliostatic but that rather the benzalkonium preservative used in clinical formulations is ciliostatic [69,70]. Regardless, azelastine does not activate NO production from the human nasal cultures, described above, and thus would not be expected to have the same immune-boosting effects as a DPD-derived compound.…”
Section: Discussionmentioning
confidence: 95%
“…(17) Mucociliary clearance also appears to be unaffected by topically administered antihistamine when applied to the nasal epithelium or trachea in vivo and in vitro. (18)(19)(20) In fact, under conditions of excess thin bronchial secretions (bronchorrhea), such as in acute asthma, there is a decrease in mucus clearance and widespread mucus obstruction contributes to small airways obstruction. Reduction of these secretions may be desirable.…”
Section: Effect Of An Antihistamine On Sputum Rheology In Cf 47mentioning
confidence: 99%